Interactive Instructional: Theoretical Perspective and Its Potential Support in Stimulating Students’ Higher Order Thinking Skills (HOTS) - Rafika Fauzia Ulfa; Habiddin Habiddin; Yudhi Utomo (Universitas Negeri Malang, 2021)
In this disruptive era, the success of teaching approaches that encourage students’ creativity and innovation is presented in students’ attained high-order thinking skills (HOTS). Consequently, the attainment of HOTS aids someone to avert negative things since they are capable of analyzing and evaluating their obtained information. Besides, HOTS also facilitates the process of students attaining knowledge, generating questions, properly interpreting information, and drawing a conclusion for an issue, with solid reasons, an open mind, and an effective means to communicate it. This article presents a theoretical study on the interactive instructional learning model and identifies its potential in accelerating students’ HOTS. It aims to introduce the interactive instructional model in chemistry learning. Further, this model can be adopted in a study with a more intensive evaluation of its empirical contribution to chemistry learning. The learning syntax for this model has been formulated for the Basic Chemistry Class 1.ReferencesBrookhart, S. M. (2010). How To Assess Higher Order thinking Skills in your classroom. Alexandria.Fearon, D. D., Copeland, D., & Saxon, T. F. (2013). The Relationship Between Parenting Styles and Creativity in a Sample of Jamaican Children. Creativity Research Journal, 25(1), 119–128. https://doi.org/10.1080/10400419.2013.752287Ghani, I. . B. ., Ibrahim, N. ., Yahaya, N. ., & Surif, J. (2017). Enhancing students’ HOTS in laboratory educational activity by using concept map as an alternative assessment tool. Chemistry Education Research and Practice, 18(4), 849–874. https://doi.org/10.1039/C7RP00120GHabiddin, H., & Page, E. M. (2020). Probing Students’ Higher Order Thinking Skills Using Pictorial Style Questions. Macedonian Journal of Chemistry and Chemical Engineering, 39(2), 251–263. https://doi.org/10.20450/mjcce.2020.2133Habiddin, H., & Page, E. M. (2021). Examining Students’ Ability to Solve Algorithmic and Pictorial Style Questions in Chemical Kinetics. International Journal of Science and Mathematics Education, 19(1), 65–85. https://doi.org/10.1007/s10763-019-10037-wHabiddin, H., & Page, E. M. (2018). Measuring Indonesian chemistry students’ Higher Order Thinking Skills (HOTS) in solving chemical kinetics questions. In Y. Rahmawati & P. C. Taylor (Eds.), Empowering Science and Mathematics for Global Competitiveness; Proceedings of the Science and Mathematics International Conference (SMIC 2018) (pp. 215–222). CRC Press Taylor & Francis.Heong, Y. M., Sern, L., Kiong, T. T., & Mohamad, M. (2016). The Role of Higher Order Thinking Skills in Green Skill Development.Herunata, H., Widarti, H. R., Amalia, R., Sulistina, O., Habiddin, H., & Rosli, M. S. bin. (2020). An analysis of higher order thinking skill (HOTs) in chemistry national examination for senior high school. AIP Conference Proceedings, 2215(1), 20009. https://doi.org/10.1063/5.0000639Horan, R. (2007). The Relationship Between Creativity and Intelligence: A Combined Yogic-Scientific Approach. Creativity Research Journal, 19(2–3), 179–202. https://doi.org/10.1080/10400410701397230Lather, A. S., Jain, S., & Shukla, A. D. (2014). Student’s Creativity in Relation to Locus of Control: a Study of Mysore University, India. The International Journal of Indian Psychȯlogy , 2(1), 146–165. http://ijip.in/article-details/?dip=18-01-058-20140201Lewis, A., & Smith, D. (1993). Defining Higher Order Thinking. Theory Into Practice, 32(3), 131–137.Lim, S., & Smith, J. (2008). The Structural Relationships of Parenting Style, Creative Personality, and Loneliness. Creativity Research Journal, 20(4), 412–419. https://doi.org/10.1080/10400410802391868McLoughlin, D., & Mynard, J. (2009). An analysis of higher order thinking in online discussions. Innovations in Education and Teaching International, 46(2), 147–160.Narciss, S. (2007). Feedback Strategies for Interactive Learning Tasks. In Handbook of Research on Educational Communications and Technology. Routledge. https://doi.org/10.4324/9780203880869.ch11Paideya, V., & Sookrajh, R. (2010). Exploring the use of supplemental instruction: Supporting deep understanding and higher-order thinking in Chemistry. South African Journal of Higher Education, 24(5), 758–770.Pannells, T. C., & Claxton, A. F. (2008). Happiness, creative ideation, and locus of control. Creativity Research Journal, 20(1), 67–71. https://doi.org/10.1080/10400410701842029Phakiti, A. (2018). Assessing Higher-Order Thinking Skills in Language Learning. In The TESOL Encyclopedia of English Language Teaching (pp. 1–7). https://doi.org/doi:10.1002/9781118784235.eelt0380Proske, A., Körndle, H., & Narciss, S. (2012). Interactive Learning Tasks BT - Encyclopedia of the Sciences of Learning (N. M. Seel (ed.); pp. 1606–1610). Springer US. https://doi.org/10.1007/978-1-4419-1428-6_1100Resnick, L. B. (1987). Education and Learning to Think. National Academy Press.Toledo, S., & Dubas, J. M. (2016). Encouraging Higher-Order Thinking in General Chemistry by Scaffolding Student Learning Using Marzano’s Taxonomy. Journal of Chemical Education, 93(1), 64–69. https://doi.org/10.1021/acs.jchemed.5b00184Zohar, A. (2004). Elements of Teachers’ Pedagogical Knowledge Regarding Instruction of Higher Order Thinking. Journal of Science Teacher Education, 15(4), 293–312. https://doi.org/10.1023/B:JSTE.0000048332.39591.e3Zohar, A., & Dori, Y. J. (2003). Higher Order Thinking Skills and Low-Achieving Students: Are They Mutually Exclusive? Journal of the Learning Sciences, 12(3), 145–181. https://doi.org/10.1207/S15327809JLS1202_1Zoller, U, & Dori, Y. J. (2002). Algorithmic, LOCS and HOCS (chemistry) exam questions: performance and attitudes of college students. International Journal of Science Education, 24(2), 185–203. https://doi.org/10.1080/09500690110049060Zoller, Uri, & Pushkin, D. (2007). Matching Higher-Order Cognitive Skills (HOCS) promotion goals with problem-based laboratory practice in a freshman organic chemistry course. Chemistry Education Research and Practice, 8(2), 153–171